A multi-scale regulated wave-absorbing geopolymer and a preparation method thereof

CN122916477APending Publication Date: 2026-10-16BOHAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611405057.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

与此同时,我国铁尾矿作为排放量最大的工业固废之一,堆存量大、综合利用率低,其露天堆存引发严重的土地侵占与环境污染问题,亟须开发兼具规模化与高附加值的资源化技术路径

Benefits of technology

1)本发明创新性地通过调控地聚物的梯度结构及微观构造,在不依赖外加吸波剂的情况下,实现了多尺度协同的电磁调控能力。构建四层梯度地聚物复合吸波结构,表层引导层采用大粒径原料优化界面阻抗匹配,降低电磁波表面反射,引导电磁波充分进入材料内部,同时耗散少量电磁波,减少进入后续层位;第二层消耗层1以大部分大颗粒搭配少量小颗粒配比,进一步削弱耗散反射波并推动电磁波向内传输,细小颗粒同步实现电磁波反射,反射后的电磁波在引导层和消耗层1的大颗粒耗散作用下进一步消耗,并且在引导层、消耗层1与入射电磁波反向叠加消耗,实现初步电磁能量衰减;第三层消耗层2采用少量大颗粒复配大部分小颗粒,依托高密度细颗粒构筑大量损耗位点和反射位点,完成绝大部分电磁波能量的核心耗散与反射,大部分小颗粒和少量大颗粒同步实现电磁波反射与耗散,反射后的电磁波在引导层、消耗层1和消耗层2的大颗粒耗散作用下进一步消耗,并且在引导层、消耗层1和消耗层2与入射电磁波反向叠加消耗,实现电磁能量大幅度衰减;底层反射层全部选用小颗粒成型,借助致密结构将未耗尽的残余电磁波反向反射至上层(引导层、消耗层1和消耗层2)依次再次吸收耗散,并且与入射电磁波在引导层、消耗层1和消耗层2反向叠加消耗,避免电磁能量外泄。该分层粒径级配设计依托自身结构排布逐级俘获、耗散电磁波,无需大量外加吸波填料,在维系地聚物整体力学性能稳定的基础上,显著提升电磁波吸收率,获得优异的电磁波吸收效能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916477A_ABST
    Figure CN122916477A_ABST
Patent Text Reader

Abstract

The application discloses a multi-scale regulated wave-absorbing geopolymer and a preparation method thereof. The geopolymer is prepared by reaction of a composite alkali activator composed of sodium silicate and sodium hydroxide without adding a wave-absorbing agent, and solid raw materials are iron tailings and blast furnace slag. The synergistic effect of the multi-layer structure of the geopolymer is utilized to simultaneously improve the compressive strength and wave-absorbing performance of the geopolymer. The multi-scale regulation mode can make the dispersion of the raw materials more uniform, improve the compressive strength of the geopolymer, and improve the consumption of electromagnetic waves in the whole frequency band under the premise of ensuring high electromagnetic wave incidence. The process flow is simple, CO2 emission is small, and the cost is low. The geopolymer can be used as a substitute for ordinary Portland cement, can reduce the influence on people in areas with more serious electromagnetic pollution, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid waste comprehensive utilization and geopolymer preparation technology, specifically to a multi-scale controlled microwave absorbing geopolymer and its preparation method. Background Technology

[0002] With the rapid development of wireless communication and electronic technologies, electromagnetic radiation has intensified, becoming a serious source of pollution affecting the safe operation of precision equipment, threatening human health, and causing the leakage of military information. Developing high-performance electromagnetic wave-absorbing building materials is of great practical significance for achieving electromagnetic protection. Meanwhile, iron tailings, as one of the largest industrial solid wastes in my country, suffer from large stockpiles and low comprehensive utilization rates. Their open-air storage causes serious land encroachment and environmental pollution problems, necessitating the development of resource utilization technologies that combine large-scale production with high added value.

[0003] Currently, the preparation of microwave-absorbing concrete mainly relies on adding microwave-absorbing agents, such as carbon materials and ferrites, to the matrix. However, this method has significant shortcomings: First, the added microwave-absorbing agents usually have poor compatibility with the cementitious system, which can damage the matrix structure and lead to a significant decrease in the mechanical properties of the material. Second, the preparation process of high-performance microwave-absorbing agents (such as core-shell nanoparticles) is complex and costly, making it difficult to meet the requirements for large-scale application in building materials. Third, a single microwave-absorbing agent is difficult to achieve effective microwave absorption across the entire frequency band from 1 to 18 GHz, especially in the low-frequency band where there are performance shortcomings. Fourth, existing technologies cannot achieve deep attenuation (reflection loss ≤ -20 dB) for specific key frequency bands (such as radar and communication bands), which cannot meet the requirements of high-protection-level scenarios. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a multi-scale controllable electromagnetic absorbing geopolymer and its preparation method. This geopolymer material uses blast furnace slag and iron tailings as substrates, and modified geopolymers are prepared by altering the gradient structure and microstructure of the geopolymer. This invention achieves high-efficiency electromagnetic absorption through multi-level structural control, eliminating the need for traditional absorbing agents. Specifically, it optimizes the gradient structure of the geopolymer to improve impedance matching and extend the electromagnetic wave propagation path. This method aims to overcome the limitations of traditional reliance on external absorbing agents, simultaneously achieving broadband high-efficiency electromagnetic absorption and targeted attenuation of specific frequencies. It provides a new approach for the high-value utilization of iron tailings and the development of novel electromagnetic absorbing building materials. The prepared geopolymer can serve as a substitute for ordinary silicate cement electromagnetic absorbing concrete, enabling the development of inexpensive and environmentally friendly electromagnetic absorbing building materials with promising application prospects.

[0005] To achieve the above technical effects, the following technical solution is adopted: A multi-scale controlled microwave absorbing geopolymer comprises the following raw materials: a guiding layer solid powder A, a consuming layer 1 solid powder B, a consuming layer 2 solid powder C, a reflective layer solid powder D, a composite alkali activator, and water. The guiding layer solid powder A consists entirely of large-particle powder a. The consuming layer 1 solid powder B is a mixture of large-particle powder a and small-particle powder b at a mass ratio of 7-8:2-3. The consuming layer 2 solid powder C is a mixture of large-particle powder a and small-particle powder b. The granular powder b is a mixed powder prepared by mixing granular powder b at a mass ratio of 2~3:7~8, and the reflective layer solid powder D is entirely composed of small granular powder b; wherein, the large granular powder a is a mixed powder prepared by mixing large granular iron tailings and large granular blast furnace slag at a mass ratio of 2~3:3~2, and the small granular powder b is a mixed powder prepared by mixing small granular iron tailings and small granular blast furnace slag at a mass ratio of 2~3:3~2; the particle size of the large granular iron tailings is 80~100 μm, the particle size of the large granular blast furnace slag is 70~90 μm, and the particle size of the small granular iron tailings and small granular blast furnace slag is 30~40 μm, and the absorbing geopolymer has a guiding layer-consumption layer 1-consumption layer 2-reflective layer structure; Furthermore, the composite alkali activator is a mixture of sodium silicate and sodium hydroxide. In each layer of raw materials, the amount of sodium silicate is 30 wt% to 50 wt% of the solid powder mass; the amount of sodium hydroxide is 1.5 wt% to 5.5 wt% of the solid powder mass. Furthermore, the iron tailings contain 25-40 wt% Al2O3 and 30-40 wt% SiO2, and are ground and sieved to obtain large and small iron tailings of corresponding particle sizes. Furthermore, the CaO content in the blast furnace slag is 20~35 wt%, and after grinding and sieving, large and small particles of blast furnace slag with corresponding particle sizes are obtained.

[0006] This invention also provides a method for preparing multi-scale controlled microwave absorbing geopolymers, comprising the following steps: Step S1: The iron tailings and blast furnace slag are crushed, ground, and sieved to separate large-diameter particles and small-diameter particles; the large-particle iron tailings and large-particle blast furnace slag are mixed at a mass ratio of 2~3:3~2 to obtain large-particle powder a, and the small-particle iron tailings and small-particle blast furnace slag are mixed at a mass ratio of 2~3:3~2 to obtain small-particle powder b. Step S2: Prepare solid powder A for the guiding layer, solid powder B for the consuming layer 1, solid powder C for the consuming layer 2, and solid powder D for the reflective layer, respectively; solid powder A for the guiding layer consists entirely of large-particle powder a, solid powder B for the consuming layer 1 is a mixed powder obtained by mixing large-particle powder a and small-particle powder b at a mass ratio of 7~8:2~3, solid powder C for the consuming layer 2 is a mixed powder obtained by mixing large-particle powder a and small-particle powder b at a mass ratio of 2~3:7~8, and solid powder D for the reflective layer consists entirely of small-particle powder b; Step S3: Sodium silicate and sodium hydroxide are added to water and dispersed evenly to obtain a composite alkali activator. The mass ratio of sodium silicate, sodium hydroxide and water is 30~50:1.5~5.5:10~30. The solid powder of the guiding layer A, the solid powder of the consuming layer 1 B, the solid powder of the consuming layer 2 C, and the solid powder of the reflective layer D are respectively mixed with the composite alkali activator and stirred for 3~15 min to obtain the guiding layer mortar C1, the consuming layer 1 mortar C2, the consuming layer 2 mortar C3 and the reflective layer mortar C4. The mortars are poured into the mold in the order of C4, C3, C2 and C1 for casting. Then, they are cured at 40~80℃ for 4~8 h to form the shape. After forming, they are cured at room temperature for 5~14 days and then demolded to obtain a wave-absorbing geopolymer with a guiding layer-consuming layer 1-consuming layer 2-reflective layer structure. Furthermore, in step S3, the amount of sodium silicate used is 30 wt% to 50 wt% of the solid powder mass; the amount of sodium hydroxide used is 1.5 wt% to 5.5 wt% of the solid powder mass. Furthermore, in the microwave absorbing geopolymer prepared in step S3, the thickness ratio of the guiding layer, the consuming layer 1, the consuming layer 2, and the reflective layer is 1:1~3:1~3:1, and the total thickness of the product is 3~5 cm; Furthermore, in the absorbing geopolymer, the thickness ratio of the guiding layer, the consuming layer 1, the consuming layer 2, and the reflective layer is 1:2:2:1, and the total thickness of the product is 4 cm; Furthermore, in step S3, each layer of mortar is left to stand for 10 to 30 minutes after being injected into the mold, and then other layers of mortar are injected. After all layers of mortar are injected into the mold, they are vibrated on a vibrating table to remove air bubbles in the mortar. Then the mold is sealed and cured to form the desired shape. Furthermore, in step S3, the vibration time is 2 to 10 minutes, after which the mold is sealed and cured.

[0007] The beneficial effects of this invention are as follows: 1) This invention innovatively achieves multi-scale synergistic electromagnetic control capabilities without relying on external absorbing agents by regulating the gradient structure and microstructure of geopolymers. A four-layer gradient geopolymer composite absorbing structure is constructed. The surface guiding layer uses large-particle raw materials to optimize interface impedance matching, reduce electromagnetic wave surface reflection, guide electromagnetic waves to fully penetrate the material interior, and simultaneously dissipate a small amount of electromagnetic waves, reducing their entry into subsequent layers. The second consumption layer 1 uses a ratio of mostly large particles to a small amount of small particles to further weaken the dissipation of reflected waves and promote electromagnetic wave propagation inward. The small particles simultaneously achieve electromagnetic wave reflection. The reflected electromagnetic waves are further consumed by the dissipation effect of the large particles in the guiding layer and consumption layer 1. Furthermore, the electromagnetic waves in the guiding layer, consumption layer 1, and incident electromagnetic waves are superimposed and consumed in opposite directions, achieving initial electromagnetic energy attenuation. The third consumption layer 2 uses a small amount of large particles combined with most small particles, relying on high-density fine particles... By constructing numerous loss and reflection sites, the core dissipation and reflection of most electromagnetic wave energy are achieved. Most small particles and a small number of large particles simultaneously reflect and dissipate electromagnetic waves. The reflected electromagnetic waves are further consumed by the large particles in the guiding layer, consumption layer 1, and consumption layer 2. Furthermore, the electromagnetic waves are superimposed on the incident electromagnetic waves in the guiding layer, consumption layer 1, and consumption layer 2, resulting in a significant attenuation of electromagnetic energy. The bottom reflective layer is entirely composed of small particles, whose dense structure reflects any remaining electromagnetic waves back to the upper layers (guiding layer, consumption layer 1, and consumption layer 2) for further absorption and dissipation. These particles are then superimposed on the incident electromagnetic waves in the guiding layer, consumption layer 1, and consumption layer 2, preventing electromagnetic energy leakage. This layered particle size distribution design captures and dissipates electromagnetic waves step-by-step based on its own structural arrangement, eliminating the need for extensive external absorbing fillers. While maintaining the overall mechanical stability of the geopolymer, it significantly improves the electromagnetic wave absorption rate, achieving excellent electromagnetic wave absorption performance.

[0008] 2) This invention fully utilizes the naturally occurring iron oxide components in solid wastes such as iron tailings and blast furnace slag. Through geological polymerization, the iron phase in the raw materials is activated and transformed into a stable phase with magnetic loss capability, forming effective intrinsic magnetic loss centers in the alkali-activated system. This method optimizes the magnetic loss performance of the material itself without introducing external magnetic materials, which not only reduces the cost of raw materials and the complexity of preparation, but also avoids the damage to the geopolymer matrix structure caused by the addition of microwave absorbers. While ensuring mechanical properties, it endows the material with excellent low-frequency electromagnetic wave absorption capability. Attached Figure Description

[0009] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. The drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0010] Figure 1 This is a photograph of the microwave-absorbing geopolymer prepared in Example 1 of the present invention; Figure 2 A physical image of the geopolymer absorbing plate prepared in Embodiment 1 of the invention; Figure 3 This is a schematic diagram of the layered structure of the geopolymer prepared in Examples 1-2 of the invention. Detailed Implementation

[0011] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0012] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0013] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, and / or combinations thereof.

[0014] In the following examples, unless otherwise specified, all reagents and consumables were purchased from conventional reagent manufacturers in the art; unless otherwise specified, the experimental methods and techniques used are conventional methods and techniques in the art.

[0015] The technical solutions provided by the present invention will be described below with reference to the embodiments. The scope of protection of the present invention is not limited by the following embodiments.

[0016] In the embodiments and comparative examples of the present invention, the large-particle iron tailings and small-particle iron tailings, after grinding and screening, have particle sizes of 80 μm and 40 μm, respectively, with Al2O3 content of 30 wt% and SiO2 content of 35 wt%; the large-particle blast furnace slag and small-particle blast furnace slag, after grinding and screening, have particle sizes of 70 μm and 40 μm, respectively, with CaO content of 25 wt%.

[0017] Equal masses of large-particle iron tailings and large-particle blast furnace slag are weighed and mixed to obtain large-particle powder a (the mass ratio of large-particle iron tailings to large-particle blast furnace slag is 1:1). Equal masses of small-particle iron tailings and small-particle blast furnace slag are weighed and mixed to obtain small-particle powder b (the mass ratio of small-particle iron tailings to small-particle blast furnace slag is 1:1).

[0018] Example 1: The raw materials prepared in this embodiment include: a guiding layer solid powder A, a consuming layer 1 solid powder B, a consuming layer 2 solid powder C, a reflective layer solid powder D, and a composite alkali activator; the guiding layer solid powder A consists entirely of large-particle powder a, the consuming layer 1 solid powder B is a mixed powder obtained by mixing large-particle powder a and small-particle powder b at a mass ratio of 7:3, the consuming layer 2 solid powder C is a mixed powder obtained by mixing large-particle powder a and small-particle powder b at a mass ratio of 3:7, and the reflective layer solid powder D consists entirely of small-particle powder b; the composite alkali activator includes sodium silicate and sodium hydroxide, in each layer of raw materials, the amount of sodium silicate added is 40 wt% of the solid powder mass, the amount of sodium hydroxide added is 3.5 wt% of the solid powder mass, and the mass ratio of water to solid powder is 0.2.

[0019] In preparation, sodium silicate and sodium hydroxide are added to water and dispersed evenly to obtain a composite alkali activator. The mass ratio of sodium silicate, sodium hydroxide, and water is 40:3.5:20. The prepared composite alkali activator is allowed to stand for 24 hours before use. Solid powder A of the guiding layer, solid powder B of the consuming layer 1, solid powder C of the consuming layer 2, and solid powder D of the reflective layer are mixed with the composite alkali activator and stirred for 5 minutes (in each layer, the amount of sodium silicate is 40 wt% of the solid powder mass, the amount of sodium hydroxide is 3.5 wt% of the solid powder mass, and the mass ratio of water to solid powder is 0.2). This yields guiding layer mortar C1, consuming layer 1 mortar C2, consuming layer 2 mortar C3, and reflective layer mortar C4. These are poured into a mold in the order of C4, C3, C2, and C1 for casting. The thickness ratio between each layer is 1:2:2:1, with a total thickness of 4 cm. Each layer of mortar is allowed to stand for 30 minutes after being poured into the mold. After the first layer of mortar is poured in, the remaining layers are then injected. Once all the mortar layers are poured into the mold, it is vibrated on a vibrating table for 10 minutes to remove air bubbles. The mold is then sealed and placed in an oven at 60°C for 6 hours to solidify. Afterward, it is removed from the oven and allowed to cure at room temperature for 7 days before demolding, yielding a geopolymer product with a guiding layer-consumption layer 1-consumption layer 2-reflective layer structure. (See also...) Figure 1-3 , Figure 1 The image shows a physical sample of the prepared microwave-absorbing geopolymer, used to test the compressive strength of the product. Figure 2 The image shows the actual product of the prepared geopolymer absorbing plate, used to test the product's microwave absorption performance. Figure 3A schematic diagram of the layered structure of the prepared geopolymer is shown.

[0020] The compressive strength of the prepared geopolymer was tested according to the national standard GB / T 50081-2019 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete". A compressive strength of 30 MPa was considered to meet the standard. The wave absorption performance of the geopolymer was tested using the bow-shaped method. The test methods for the remaining examples and comparative examples were the same as those in Example 1.

[0021] Example 2: The raw materials prepared in this embodiment include: a guiding layer solid powder A, a consumption layer 1 solid powder B, a consumption layer 2 solid powder C, a reflective layer solid powder D, and a composite alkali activator; the guiding layer solid powder A is entirely composed of large particle powder a, the consumption layer 1 solid powder B is a mixed powder obtained by mixing large particle powder a and small particle powder b at a mass ratio of 8:2, the consumption layer 2 solid powder C is a mixed powder obtained by mixing large particle powder a and small particle powder b at a mass ratio of 2:8, and the reflective layer solid powder D is entirely composed of small particle powder b.

[0022] Except for the different solid powder compositions of the above-mentioned consumption layer 1 and consumption layer 2, the other raw material compositions and preparation methods are the same as those in Example 1. For specific preparation methods, please refer to Example 1.

[0023] Comparative Example 1: The raw materials prepared in this embodiment include: a guiding layer solid powder A, a consuming layer 1 solid powder B, a consuming layer 2 solid powder C, a reflective layer solid powder D, and a composite alkali activator; the guiding layer solid powder A consists entirely of large particle powder a, the consuming layer 1 solid powder B is a mixed powder obtained by mixing large particle powder a and small particle powder b at a mass ratio of 3:7, the consuming layer 2 solid powder C is a mixed powder obtained by mixing large particle powder a and small particle powder b at a mass ratio of 7:3, and the reflective layer solid powder D consists entirely of small particle powder b.

[0024] Except for the different solid powder compositions of the above-mentioned consumption layer 1 and consumption layer 2, the other raw material compositions and preparation methods are the same as those in Example 1. For specific preparation methods, please refer to Example 1.

[0025] Comparative Example 2: The raw materials prepared in this embodiment include: a guiding layer solid powder A, a consumption layer 1 solid powder B, a consumption layer 2 solid powder C, a reflective layer solid powder D, and a composite alkali activator; the guiding layer solid powder A is a mixed powder obtained by mixing large particle powder a and small particle powder b at a mass ratio of 7:3; the consumption layer 1 solid powder B is entirely composed of large particle powder a; the consumption layer 2 solid powder C is a mixed powder obtained by mixing large particle powder a and small particle powder b at a mass ratio of 3:7; and the reflective layer solid powder D is entirely composed of small particle powder b.

[0026] Except for the different solid powder compositions of the guiding layer and the consumption layer 1, the other raw material compositions and preparation methods are the same as in Example 1. For specific preparation methods, please refer to Example 1.

[0027] Comparative Example 3: The raw materials prepared in this embodiment include: a guiding layer solid powder A, a consuming layer 1 solid powder B, a consuming layer 2 solid powder C, a reflective layer solid powder D, and a composite alkali activator; the guiding layer solid powder A is a mixed powder obtained by mixing large particle powder a and small particle powder b at a mass ratio of 7:3, the consuming layer 1 solid powder B is a mixed powder obtained by mixing large particle powder a and small particle powder b at a mass ratio of 3:7, the consuming layer 2 solid powder C is entirely composed of large particle powder a, and the reflective layer solid powder D is entirely composed of small particle powder b.

[0028] Except for the different solid powder compositions of the above-mentioned guiding layer, consumption layer 1 and consumption layer 2, the other raw material compositions and preparation methods are the same as those in Example 1. For specific preparation methods, please refer to Example 1.

[0029] Comparative Example 4: The raw materials prepared in this embodiment include: a guiding layer solid powder A, a consumption layer 1 solid powder B, a consumption layer 2 solid powder C, a reflective layer solid powder D, and a composite alkali activator; the guiding layer solid powder A is a mixed powder obtained by mixing large particle powder a and small particle powder b at a mass ratio of 3:7, the consumption layer 1 solid powder B is entirely composed of large particle powder a, the consumption layer 2 solid powder C is a mixed powder obtained by mixing large particle powder a and small particle powder b at a mass ratio of 7:3, and the reflective layer solid powder D is entirely composed of small particle powder b.

[0030] Except for the different solid powder compositions of the above-mentioned guiding layer, consumption layer 1 and consumption layer 2, the other raw material compositions and preparation methods are the same as those in Example 1. For specific preparation methods, please refer to Example 1.

[0031] Comparative Example 5: The raw materials prepared in this embodiment include: a guiding layer solid powder A, a consuming layer 1 solid powder B, a consuming layer 2 solid powder C, a reflective layer solid powder D, and a composite alkali activator; the guiding layer solid powder A is a mixed powder obtained by mixing large particle powder a and small particle powder b at a mass ratio of 3:7, the consuming layer 1 solid powder B is a mixed powder obtained by mixing large particle powder a and small particle powder b at a mass ratio of 7:3, the consuming layer 2 solid powder C is entirely composed of large particle powder a, and the reflective layer solid powder D is entirely composed of small particle powder b.

[0032] Except for the different solid powder compositions of the guiding layer and the consumption layer 2, the other raw material compositions and preparation methods are the same as in Example 1. For specific preparation methods, please refer to Example 1.

[0033] Comparative Example 6: The raw materials prepared in this embodiment include: solid powder A for the guiding layer, solid powder B for the consuming layer 1, solid powder C for the consuming layer 2, solid powder D for the reflective layer, and a composite alkali activator; the solid powder A for the guiding layer, solid powder B for the consuming layer 1, and solid powder C for the consuming layer 2 are all large-particle powder a, and the solid powder D for the reflective layer is all small-particle powder b.

[0034] Except for the different solid powder compositions of the above-mentioned consumption layer 1 and consumption layer 2, the other raw material compositions and preparation methods are the same as those in Example 1. For specific preparation methods, please refer to Example 1.

[0035] Comparative Example 7: The raw materials prepared in this embodiment include: solid powder A for the guiding layer, solid powder B for the consuming layer 1, solid powder C for the consuming layer 2, solid powder D for the reflective layer, and a composite alkali activator; all of the solid powders A for the guiding layer, B for the consuming layer 1, C for the consuming layer 2, and D for the reflective layer are small particle powders b.

[0036] Except for the different solid powder compositions of the above-mentioned guiding layer, consumption layer 1 and consumption layer 2, the other raw material compositions and preparation methods are the same as those in Example 1. For specific preparation methods, please refer to Example 1.

[0037] Comparative Example 8: The raw materials prepared in this embodiment include: solid powder A for the guiding layer, solid powder B for the consuming layer 1, solid powder C for the consuming layer 2, solid powder D for the reflective layer, and a composite alkali activator; the solid powder A for the guiding layer, solid powder B for the consuming layer 1, and solid powder C for the consuming layer 2 are all mixed powders prepared by mixing large particle powder a and small particle powder b in a mass ratio of 7:3, and the solid powder D for the reflective layer is entirely composed of small particle powder b.

[0038] Except for the different solid powder compositions of the guiding layer and the consumption layer 2, the other raw material compositions and preparation methods are the same as in Example 1. For specific preparation methods, please refer to Example 1.

[0039] Comparative Example 9: The raw materials prepared in this embodiment include: solid powder A for the guiding layer, solid powder B for the consuming layer 1, solid powder C for the consuming layer 2, solid powder D for the reflective layer, and a composite alkali activator; the solid powder A for the guiding layer, solid powder B for the consuming layer 1, and solid powder C for the consuming layer 2 are all mixed powders prepared by mixing large particle powder a and small particle powder b in a mass ratio of 3:7, and the solid powder D for the reflective layer is entirely composed of small particle powder b.

[0040] Except for the different solid powder compositions of the guiding layer and the consumption layer 1, the other raw material compositions and preparation methods are the same as in Example 1. For specific preparation methods, please refer to Example 1.

[0041] Comparative Example 10: The raw materials prepared in this embodiment include: solid powder A for the guiding layer, solid powder B for the consuming layer 1, solid powder C for the consuming layer 2, solid powder D for the reflective layer, and a composite alkali activator; solid powder A for the guiding layer is entirely composed of large-particle powder a, solid powder B for the consuming layer 1 and solid powder C for the consuming layer 2 are both mixed powders prepared by mixing large-particle powder a and small-particle powder b in a mass ratio of 3:7, and solid powder D for the reflective layer is entirely composed of small-particle powder b.

[0042] Except for the different composition of the solid powder in the above-mentioned consumption layer 1, the composition of other raw materials and the preparation method are the same as in Example 1. For the specific preparation method, please refer to Example 1.

[0043] Comparative Example 11: The raw materials prepared in this embodiment include: solid powder A for the guiding layer, solid powder B for the consuming layer 1, solid powder C for the consuming layer 2, solid powder D for the reflective layer, and a composite alkali activator; the solid powder A for the guiding layer is entirely composed of large-particle powder a, the solid powder B for the consuming layer 1 and the solid powder C for the consuming layer 2 are both mixed powders prepared by mixing large-particle powder a and small-particle powder b in a mass ratio of 7:3, and the solid powder D for the reflective layer is entirely composed of small-particle powder b.

[0044] Except for the different composition of the solid powder in the above-mentioned consumption layer 2, the composition of other raw materials and the preparation method are the same as in Example 1. For the specific preparation method, please refer to Example 1.

[0045] Comparative Example 12: The raw materials prepared in this embodiment include: solid powder A for the guiding layer, solid powder B for the consuming layer 1, solid powder C for the consuming layer 2, solid powder D for the reflective layer, and a composite alkali activator; the solid powder A for the guiding layer is entirely composed of large-particle powder a, the solid powder B for the consuming layer 1 and the solid powder C for the consuming layer 2 are both mixed powders prepared by mixing large-particle powder a and small-particle powder b in a mass ratio of 1:1, and the solid powder D for the reflective layer is entirely composed of small-particle powder b.

[0046] Except for the different solid powder compositions of the above-mentioned consumption layer 1 and consumption layer 2, the other raw material compositions and preparation methods are the same as those in Example 1. For specific preparation methods, please refer to Example 1.

[0047] The microwave absorption properties and compressive strength of the geopolymers prepared in Examples 1-2 and Comparative Examples 1-12 were tested, and the results are shown in Table 1.

[0048] Table 1. Compressive strength and microwave absorption effect of geopolymers prepared in the examples and comparative examples.

[0049] As can be seen from the data in Table 1, Examples 1-2 of this invention used iron tailings and blast furnace slag as solid powders for preparing geopolymers, and employed a composite alkali activator of sodium silicate and sodium hydroxide to prepare geopolymers with different gradient layered structures (guide layer-consumption layer 1-consumption layer 2-reflective layer structure). Utilizing the synergistic effect of the multi-level structure, the compressive strength and microwave absorption performance of the geopolymers can be improved simultaneously. Specifically, the compressive strengths of the geopolymer products prepared in Examples 1 and 2 were 55 MPa and 52 MPa, respectively; the maximum reflection losses were -57.1 dB and -53.9 dB, respectively; and the microwave absorption bandwidths were 17.9 dB and 17.9 dB, respectively. Compared to Comparative Examples 1-12, the compressive strength and wave absorption performance of the geopolymer products prepared in Examples 1-2 are significantly improved at GHz and 17.3GHz. However, when the arrangement order of different layers in the geopolymer products of Comparative Examples 1-12 is adjusted, their compressive strength and wave absorption performance decrease significantly. This indicates that the geopolymer with a specific layered structure arrangement order prepared in Examples 1-2 can significantly improve the compressive strength and wave absorption performance of the geopolymer, giving the material excellent electromagnetic wave absorption capability while ensuring mechanical properties. The geopolymer product with a guiding layer-consumption layer 1-consumption layer 2-reflective layer structure prepared by this invention, as a wave-absorbing concrete, can not only reduce carbon emissions, but also prevent electromagnetic pollution and prevent information leakage.

[0050] Therefore, those skilled in the art will recognize that although embodiments of the present invention have been shown and described in detail herein, many other variations or modifications conforming to the principles of the present invention can be directly determined or derived from the disclosure of the present invention without departing from the spirit and scope of the invention. Thus, the scope of the present invention should be understood and recognized as covering all such other variations or modifications.

Claims

1. A multi-scale tunable microwave absorbing geopolymer, characterized in that, The raw materials include: guiding layer solid powder A, consumption layer 1 solid powder B, consumption layer 2 solid powder C, reflective layer solid powder D, composite alkali activator, and water. The guiding layer solid powder A consists entirely of large-particle powder a. The consumption layer 1 solid powder B is a mixture of large-particle powder a and small-particle powder b at a mass ratio of 7-8:2-3. The consumption layer 2 solid powder C is a mixture of large-particle powder a and small-particle powder b at a mass ratio of 2-3:7-8. The reflective layer solid powder D consists entirely of small-particle powder b. Specifically, the large-particle powder a is a mixture of large-particle iron tailings and large-particle blast furnace slag at a mass ratio of 2-3:3-2, and the small-particle powder b is a mixture of small-particle iron tailings and small-particle blast furnace slag at a mass ratio of 2-3:3-2. The large-particle iron tailings have a particle size of 80-100 mm. The particle size of the large blast furnace slag is 70~90 μm, and the particle size of the small iron tailings and small blast furnace slag is 30~40 μm. The absorbing geopolymer has a guiding layer-consumption layer 1-consumption layer 2-reflective layer structure.

2. The multi-scale tunable absorbing geopolymer as described in claim 1, characterized in that, The composite alkali activator is a mixture of sodium silicate and sodium hydroxide. In each layer of raw materials, the amount of sodium silicate is 30 wt% to 50 wt% of the solid powder mass, and the amount of sodium hydroxide is 1.5 wt% to 5.5 wt% of the solid powder mass.

3. The multi-scale tunable absorbing geopolymer as described in claim 1, characterized in that, The iron tailings contain 25-40 wt% Al2O3 and 30-40 wt% SiO2. After grinding and sieving, large and small iron tailings of corresponding particle sizes are obtained.

4. The multi-scale tunable absorbing geopolymer as described in claim 1, characterized in that, The blast furnace slag contains 20-35 wt% CaO, and after grinding and sieving, large and small particles of blast furnace slag with corresponding particle sizes are obtained.

5. A method for preparing a multi-scale controlled microwave absorbing geopolymer as described in claims 1-4, characterized in that, Includes the following steps: Step S1: The iron tailings and blast furnace slag are crushed, ground, and sieved to separate large-diameter particles and small-diameter particles; the large-particle iron tailings and large-particle blast furnace slag are mixed at a mass ratio of 2~3:3~2 to obtain large-particle powder a, and the small-particle iron tailings and small-particle blast furnace slag are mixed at a mass ratio of 2~3:3~2 to obtain small-particle powder b. Step S2: Prepare solid powder A for the guiding layer, solid powder B for the consuming layer 1, solid powder C for the consuming layer 2, and solid powder D for the reflective layer, respectively; solid powder A for the guiding layer consists entirely of large-particle powder a, solid powder B for the consuming layer 1 is a mixed powder obtained by mixing large-particle powder a and small-particle powder b at a mass ratio of 7~8:2~3, solid powder C for the consuming layer 2 is a mixed powder obtained by mixing large-particle powder a and small-particle powder b at a mass ratio of 2~3:7~8, and solid powder D for the reflective layer consists entirely of small-particle powder b; Step S3: Sodium silicate and sodium hydroxide are added to water and dispersed evenly to obtain a composite alkali activator. The mass ratio of sodium silicate, sodium hydroxide and water is 30~50:1.5~5.5:10~30. The solid powder of the guiding layer A, the solid powder of the consuming layer 1 B, the solid powder of the consuming layer 2 C, and the solid powder of the reflective layer D are mixed with the composite alkali activator and stirred for 3~15 min to obtain the guiding layer mortar C1, the consuming layer 1 mortar C2, the consuming layer 2 mortar C3 and the reflective layer mortar C4. The mortars are poured into the mold in the order of C4, C3, C2 and C1 for casting. Then, they are cured at 40~80℃ for 4~8 h to form the mortar. After forming, they are cured at room temperature for 5~14 days and then demolded to obtain a wave-absorbing geopolymer with a guiding layer-consuming layer 1-consuming layer 2-reflective layer structure.

6. The method for preparing a multi-scale controlled microwave absorbing geopolymer as described in claim 5, characterized in that, In step S3, the amount of sodium silicate used is 30 wt% to 50 wt% of the solid powder mass; the amount of sodium hydroxide used is 1.5 wt% to 5.5 wt% of the solid powder mass.

7. The method for preparing a multi-scale controlled microwave absorbing geopolymer as described in claim 5, characterized in that, In the microwave absorbing geopolymer prepared in step S3, the thickness ratio of the guiding layer, the consuming layer 1, the consuming layer 2, and the reflective layer is 1:1~3:1~3:1, and the total thickness of the product is 3~5 cm.

8. The method for preparing a multi-scale controlled microwave absorbing geopolymer as described in claim 7, characterized in that, In the absorbing geopolymer, the thickness ratio of the guiding layer, the consuming layer 1, the consuming layer 2, and the reflecting layer is 1:2:2:1, and the total thickness of the absorbing geopolymer is 4 cm.

9. The method for preparing a multi-scale controlled microwave absorbing geopolymer as described in claim 5, characterized in that, In step S3, each layer of mortar is left to stand for 10 to 30 minutes after being poured into the mold, and then other layers of mortar are poured in. After all the layers of mortar are poured into the mold, they are vibrated on a vibrating table to remove air bubbles in the mortar. Then the mold is sealed and cured to form the desired shape.

10. The method for preparing a multi-scale controlled microwave absorbing geopolymer as described in claim 9, characterized in that, In step S3, the vibration time is 2~10 min, after which the mold is sealed and cured.